The Interpolative Ideal of Bloch Mappings - D. Achour; M. G. Cabrera-Padilla; A. Jiménez-Vargas (Journal of Function Spaces)
Inspired by the interpolative ideal procedure for linear operators due to Matter, the concept of interpolative ideals of a Banach normalized Bloch ideal IB∧ is introduced. For σ∈0,1, we prove that the generated ideal IB∧σ is an injective Banach normalized Bloch ideal which is located between the injective hull and the closed injective hull of IB∧. We apply this interpolative procedure to normalized Bloch ideals generated by composition and duality. In particular, normalized Bloch ideals generated by composition with p-summing operator ideals are characterized in terms of a Pietsch-type domination property and a summability property.